2017
DOI: 10.1038/s41598-017-10412-z
|View full text |Cite
|
Sign up to set email alerts
|

Global organization of a binding site network gives insight into evolution and structure-function relationships of proteins

Abstract: The global organization of protein binding sites is analyzed by constructing a weighted network of binding sites based on their structural similarities and detecting communities of structurally similar binding sites based on the minimum description length principle. The analysis reveals that there are two central binding site communities that play the roles of the network hubs of smaller peripheral communities. The sizes of communities follow a power-law distribution, which indicates that the binding sites inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…The next significantly enriched fold (p=3.1e‐12) corresponds to the NAD(P) – binding Rossmann‐fold domains (c.2 fold). This agrees with the findings on the protein‐small molecule binding site similarity network), where this fold was found as one of the most ancient. The agreement of our results with previous studies suggests that protein‐ion binding site network and protein‐compound binding network are related, and that they most likely co‐evolve with each other.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The next significantly enriched fold (p=3.1e‐12) corresponds to the NAD(P) – binding Rossmann‐fold domains (c.2 fold). This agrees with the findings on the protein‐small molecule binding site similarity network), where this fold was found as one of the most ancient. The agreement of our results with previous studies suggests that protein‐ion binding site network and protein‐compound binding network are related, and that they most likely co‐evolve with each other.…”
Section: Resultssupporting
confidence: 92%
“…Although existing studies provide possible mechanistic explanations on the level of protein domain networks, there are currently very few reports on evolution of protein binding sites. Recently, global small molecule (compound) binding site similarity network was investigated, where the compound binding site community network was found to be scale‐free, thus, a few of communities covering the majority of the network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins largely function to bind to other molecules, whether small molecules, proteins, or other macromolecules. Past work has shown that binding sites can reveal evolutionary relationships among proteins [42] and that particular structural motifs in binding sites are mainly restricted to specific families or superfamilies of proteins [37]. Thus binding sites provide a high-level characterization of the protein that may be relevant for the model throughout the sequence.…”
Section: Binding Sitesmentioning
confidence: 99%
“…Proteins largely function to bind to other molecules, whether small molecules, proteins, or other macromolecules. Past work has shown that binding sites can reveal evolutionary relationships among proteins [40] and that particular structural motifs in binding sites are mainly restricted to specific families or superfamilies of proteins [35]. Thus binding sites provide a high-level characterization of the protein that may be relevant for the model throughout the sequence.…”
Section: Binding Sitesmentioning
confidence: 99%